2016
DOI: 10.1242/jcs.193946
|View full text |Cite
|
Sign up to set email alerts
|

Bok is a genuine multi-BH-domain protein that triggers apoptosis in the absence of Bax and Bak

Abstract: There was an error published in J. Cell Sci. 129, 2213-2223.In Fig. 4A, a statement that duplicate α-tubulin blots are shown for Mcl-1 and Bok, and for caspase-3 and Bax, because the same membranes were probed for these proteins, was inadvertently omitted from the legend.The authors apologise to the readers for any confusion that this error might have caused. 3054

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 0 publications
4
43
1
Order By: Relevance
“…c release from enriched mitochondrial fractions derived from Bax −/− Bak −/− MEFs, not even when cBID was added or heat was provided to the reaction mixture. This result contrasts with reports that BOK can trigger the intrinsic apoptotic pathway independently of BAX/BAK . However, neither of those studies provided direct proof of cyt.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…c release from enriched mitochondrial fractions derived from Bax −/− Bak −/− MEFs, not even when cBID was added or heat was provided to the reaction mixture. This result contrasts with reports that BOK can trigger the intrinsic apoptotic pathway independently of BAX/BAK . However, neither of those studies provided direct proof of cyt.…”
Section: Discussioncontrasting
confidence: 96%
“…BOK remains an enigmatic and controversial protein among the BCL‐2 members. In accordance with its sequence homology with BAX/BAK, multiple studies, including our own work, demonstrated that BOK promotes intrinsic apoptosis upon overexpression . However, both BAX/BAK‐dependent as well as BAX/BAK‐independent mechanisms have been proposed since .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This study also suggests that Bok deficiency leads to decreased ER stress signaling, potentially through the regulation of calcium release [82]. More recent findings support a selective and distinguishing role for BOK in regulating the apoptotic response to ER and proteasomal stressors, and show evidence that BOK is fully competent to promote MOMP in the absence of BAK/BAX and BH3-only proteins [83] [81]. …”
Section: Figurementioning
confidence: 63%
“…Recent insights into the chemotherapeutic responses of ovarian cancer cells also point to a BAK/BAX-independent role for BOK in mediating MOMP and apoptosis [83]. At present, we have neither structural information nor any details pertaining to how mitochondria may regulate BOK.…”
Section: Figurementioning
confidence: 98%